Men’s gender role and attitude toward sexual autonomy of women in India - Manas Ranjan Pradhan; Prasenjit De (PLoS ONE, 2025)
Objective Sexual autonomy is essential to women’s empowerment and crucial to human rights. Measurement of women’s sexual autonomy from men’s perspective is rare in India, though critical for achieving the sexual and reproductive rights of women who continue to exhibit poor sexual and reproductive health (SRH) outcomes. The study assesses Indian men’s attitudes toward women’s sexual autonomy and associated factors using a nationally representative sample of men. Methods This study involved a total sample of 101,839 men aged 15–54 covered in the fifth round of the National Family Health Survey (2019–21). Descriptive statistics, bivariate analysis, and binary logistic regression were used to determine predictors of men’s favorable attitudes toward the sexual autonomy of women. All the statistical analyses were performed using Stata with a 5% significance level. Results Sixty-three percent of men hold a favorable attitude toward women’s sexual autonomy. Men’s support for women’s sexual autonomy was positively correlated with their egalitarian views on household decision-making (AOR: 1.45; CI: 1.41–1.49), higher educational attainment (AOR: 1.34; CI:1.20–1.50), currently married status, media exposure (AOR: 1.17; CI: 1.12–1.21), currently working status, and wealthier household strata (AOR: 1.17; CI: 1.11–1.23). Conclusion Results suggest promoting gender egalitarian norms through educational campaigns, community workshops held by local leaders, grassroots healthcare professionals, and non-governmental organizations, and broadening existing SRH strategies by including younger, non-literates, unmarried, unemployed, and rural men.